Peran Internasional Civil Aviation Organization Dalam Investasi Kecelakaan Penerbangan Internasional Studi Kasus Mh17 Antara Ukraina Dan Rusia - Mutiara Indryanti; Andoly Rafhael Sitorus; Muhammad Zalfie Habibie; M.Ilham Adepio (GLOBAL SCIENTS PUBLISHER, 2026)
This article aims to analyze the role of the International Civil Aviation Organization (ICAO) in the investigation of international aviation accidents through the case study of Malaysia Airlines Flight MH17, which crashed in the airspace of Ukraina in 2014. This research employs a normative juridical method using an approach based on international regulations and case studies. Based on the Chicago Convention 1944, particularly Annex 13, ICAO plays a role in establishing standards and procedures for aircraft accident investigations. The findings indicate that ICAO has an important function in coordinating between states and formulating international aviation safety standards. However, ICAO does not have the authority to impose sanctions on states, which limits its role to providing recommendations. The MH17 case demonstrates that in conflict areas, the effectiveness of ICAO remains limited.